Sensitivity of Senepol and Caracu breeds to parasitism by Rhipicephalus microplus - Piña, Francisco Tobias Barradas; Zimmermann, Namor Pinheiro; Garcia, Marcos Valério; Higa, Leandro De Oliveira Souza; Oshiro, Leandra Marla; Duarte, Pâmela Oliveira; Barros, Jacqueline Cavalcante; Andreotti, Renato (Systematic and applied acarology, 2021)
Taurine breeds and animals crossbred for genetic resistance to Rhipicephalus microplus have been the focus of several studies aimed at producing better responses of cattle to tick infestations and seeking to reduce treatment costs and improve the quality of bovine byproducts. Another way to increase gains is the introduction of taurine breeds with the goal of obtaining morphological and physiological characteristics more adapted to production. Although several studies have compared taurine and zebu breeds, little is known about the differences found within the taurine group. Therefore, the present study aimed to evaluate the sensitivity of the Senepol and Caracu breeds to artificial R. microplus infestations. For this purpose, a stall test was conducted on 16 Caracu and 14 Senepol bulls. The animals were subjected to artificial infestation with a total of 15,000 R. microplus larvae per animal. The Senepol group accounted for 71.7% of the retrieved engorged female ticks. The biological parameters analyzed that showed a significant difference included the mean number of engorged female ticks retrieved (p = 0.000), weight of engorged female ticks (p = 0.000), rate of engorged female ticks retrieved (p = 0.03) and egg mass weight (p = 0.032). Thus, the present study demonst          rated a higher susceptib ility of the Senepol breed to parasitism by the Asian blue tick than the Caracu breed, providing support for new studies on the subjects of genetic resistance, animal breeding and cattle production.